Supplementation of an all-plant-based inorganic phosphate-free diet with a novel phytase maintained tibia ash and performance in broilers under a commercial production setting - A. Bello; Y. Dersjant-Li; E. van Eerden; C. Kwakernaak; L. Marchal (Journal of Applied Poultry Research, 2022)
SUMMARY: Removal of inorganic phosphate (Pi) from broiler diets could improve sustainability in poultry production. Small-scale studies of total Pi replacement by a novel consensus bacterial 6-phytase variant have been promising but larger scale studies are needed. In this study, effects of 4 diets on growth performance and bone quality were evaluated: PC1, nutritionally adequate and containing Pi without enzyme supplementation; PC2, as PC1 but containing xylanase (2,000 units [XU]/kg) and 75 kcal/kg reduction in ME; IPF1 and IPF2, as PC1 and PC2, respectively, formulated without Pi and 1.5 g/kg reduction in Ca, containing phytase at 3,000, 2,000, and 1,000 phytase units (FTU)/kg during starter (1–10 d), grower (10–22 d), and finisher (22–37 d) phases. A randomized complete block design used 820 Ross 308 mixed-sex birds/pen and 8 pens/diet. The phytase in IPF diets maintained all growth performance parameters, per phase and cumulatively, equivalent to the respective PC. Contrast analysis of pooled PC vs. pooled IPF data showed that phytase in IPF diets reduced or maintained FCR during all phases and cumulatively (−5.0 points during 22–37 d and −3.0 points during 1–37 d; P < 0.05). Tibia ash at d 21 and 36 was not different in birds fed IPF and PC diets, but tibia breaking strength was higher in birds fed IPF diets (+6.6% and +1.3%, respectively; P < 0.05). Overall (0–37 d), total feed costs per kilogram BW gain were reduced (P < 0.05) in the phytase supplemented IPF diets vs. PC diets under commercial broiler production conditions.